"Elsa, Why are you in Fear and Anger?": The Power of Magic and Control of Emotion in Frozen - Park, Eun Jung (Journal of Digital Contents Society, 2016)
This paper has the first aim to analyze Elsa’s magic power of why and how she, as a heroine in the animation of Frozen, is in the emotion of fear and anger. This paper will explain why these two emotions are twisted compound to identify Elsa’s iced emotion in the ice kingdom. And secondly, this paper attempts to connect Elsa’s fear emotion in her real life is the other flip with that of anger throughout the characters' network in Frozen, which symbolically reflect the feminine pattern of real society that Walt Disney prospects for the dream society. Through the cognitive process for Elsa’s ice kingdom between emotion status and social network, we can assume the pattern of social network with emotional chart and the archetype of human emotion through the cognitive-emotional storytelling on the emotion of Elsa in Frozen. KCI Citation Count: 1